2005
DOI: 10.1353/sof.2006.0027
|View full text |Cite
|
Sign up to set email alerts
|

Student Disengagement and the Socialization Styles of High Schools

Abstract: This paper advances a cross-contextual understanding of authoritative socialization, a concept developed by family researchers. Using data from the High School Effectiveness Study, I use multilevel modeling to test the effect of high school socialization style on student disengagement from 10`h to 12th grades, controlling for both the sociodemographic context of schools and student characteristics. Ifind that school socialization style is differentially associated with student disengagement by 10" grade, and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
1
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 41 publications
2
34
1
1
Order By: Relevance
“…In addition to educational attainment or aspiration, researchers have been interested in student disengagement indicated by school attendance and punishment as an important dimension of educational outcomes, exploring individual-level and school-level determinants of student disengagement (Pellerin, 2005; National Research Council and the Institute of Medicine, 2004). Punishment is a straightforward measure of students' misbehavior in schools.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to educational attainment or aspiration, researchers have been interested in student disengagement indicated by school attendance and punishment as an important dimension of educational outcomes, exploring individual-level and school-level determinants of student disengagement (Pellerin, 2005; National Research Council and the Institute of Medicine, 2004). Punishment is a straightforward measure of students' misbehavior in schools.…”
Section: Methodsmentioning
confidence: 99%
“…This topic, however, gets extra attention in schools that serve minority students living in poverty (Pellerin, 2005). Specifically, disruptive behavior is often identified by urban teachers as one of the major barriers to both teaching and learning.…”
mentioning
confidence: 99%
“…A substantial body of literature has examined the leadership styles that lend themselves to caring school environments, and the impact these relationships have on students' academic outcomes (e.g., Fullan, 2001Fullan, , 2002Nell, 2012). Ethical, transformational, authoritative, and reciprocal leadership styles have been found to lend themselves to more caring school environments, while authoritarian and transactional leadership styles are detrimental to the building of caring communities in schools (Eagly & Johannesen-Schmidt, 2001;Follett, 1919Follett, , 1917Follett, /2003Mandell & Pherwani, 2003;Pellerin, 2005;Shapiro & Stefkovich, 2011). Studies examining caring in schools have found that administrative leaders in caring communities are accessible to teachers and students, forge supportive, trusting relationships with faculty, provide teachers autonomy in how they teach, give teachers a voice in school decision-making, and build time into the schedule for teachers to build relationships with students and the local community (Ancess, 2003;Dantley & Tillman, 2010;Jacobson et al, 2007;Johnson, 2009;McQuillan, 1997;Rivera-McCutchen & Watson, 2014;Shields, 2010;Theoharis, 2009).…”
Section: Leadershipmentioning
confidence: 99%